The effectiveness of the Family Health Strategy and the Directly Observed Treatment in Tuberculosis control - Baldan, Sueli Santiago; Ferraudo, Antonio Sergio [UNESP]; Andrade, Monica de (Univ Santa Cruz Do Sul, 2016)
Background and objectives: The consolidation of Primary Health Care, making it the leading role in the care of the individual with tuberculosis, favors the identification of respiratory symptoms, as well as the diagnosis and early treatment, reducing disease transmission and promoting treatment adherence. This study aimed to investigate the effectiveness of the Family Health Strategy - FHS - coverage and the Directly Observed Treatment Strategy - DOTS in the control of non-adherence to tuberculosis treatment. Methods: Exploratory study, based on secondary data. The investigated variables were: TB incidence rate (CI-TB), percentage of coverage by the FHS, treatment abandonment rate and percentage of DOTS offered in the state of Mato Grosso do Sul. The hierarchical cluster analysis method was used to look for patterns contained in the data set. Results: The data indicate that there are groups of municipalities in which the coverage by FHS and DOTS contributes to treatment adherence and control of the number of TB cases, while in other municipalities these measures have not been effective in reducing CI-TB and treatment abandonment rate. The disease is heterogeneously distributed in the state. Conclusion: Professionals and health managers need to be aware of TB patterns in their regions, prioritizing and planning actions that contribute to an effective control of the disease transmission, and to greater treatment adherence in their community.
Keywords: Tuberculosis; Directly Observed Treatment; Family Health Strategy; Treatment adherence